Anmeldelser - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 1997)
Review of: F.L.Ae. Kunzen og Jens Baggesen: Holger Danske. Inga Nielsen (Oberon), Henriette Bonde-Hansen (Titania), Inger Dam Jensen (Rezia), Marianne Rørholm (Almansaris), Gert Henning-Jensen (Holger), Johannes Mannov (Kerasmin), Johan Reuter (Buurman/Bobul), Guido Paëvatalu (Muftien), Radiosymfoniorkestret, Radiokoret, Thomas Dausgaard (dirigent). dacapo 8.224036-37.